Adverse Selection and Private Health Insurance Coverage in India : A Rational Behaviour Model of Insurance Agents under Asymmetric Information - Sukumar Vellakkal (Indian Council for Research on International Economic Relations (ICRIER), 2009)
In the backdrop of the low level of health insurance coverage in India, this study examines the determinants of the scaling-up process of health insurance by analyzing the rational behaviour of an insurance agent facing a trade-off between selling 'health insurance' and 'other forms of insurance' subject to his limited time and efforts, and the implications of such behaviour on adverse selection and equity. The paper presents various pre-conditions affecting the rational behaviour of insurance agents and also discusses two new concepts- 'insurance habit' and 'asymmetric information on health insurance schemes'. Further, the study examines various strategies followed by insurance agents for maximizing their net incomes. The theoretical proposition is empirically validated by applying a binary Probit model and the primary data collected by the author is used in this context. The study concludes that given the existing incentive systems in the Indian insurance market for promoting various forms of insurance, the low level of insurance awareness among the general public, coupled with the dominant role of insurance agents in the market results in a situation of: 1. Low level of health insurance coverage, 2. No adverse selection and 3. Inequity in health insurance coverage.
Keywords: I11; D82; 330; Health Insurance; Insurance Agent; Asymmetric Information; Adverse Selection and Insurance Habit; Private Krankenversicherung; Asymmetrische Information; Adverse Selektion; Rationalität; Privater Haushalt; Indien